(Un)making a Monster: Melodrama, The Satirist, and the Cartoons of Samuel De Wilde. Issue 2 (November 2021) - Mayer, David; Gamer, Michael
Our essay takes up the well-known satirical print, 'The Monster Melo-Drame', and re-attaches it to several contexts to bring forward its richness and ambiguity as an image. We begin by considering its artist (Samuel De Wilde), printer (Samuel Tipper), and publisher ( The Satirist ), interpreting the print in its original publication and in dialogue with the essay that accompanied it in the January 1808 issue of the Satirist . The image, we argue, should not be read on its own but rather as the first of a trio of prints De Wilde made for that magazine. Taken together, the images show the Satirist engaging in a sustained campaign against London's Theatres Royal, one in which melodrama is a subject but not a primary target. Part of our essay's work is necessarily that of description: identifying figures, references, and tableaux as these prints comment on a rapidly changing theatrical scene between 1807 and 1809. Considered as a set, De Wilde's prints constituted a fundamental part of the Satirist's attacks on the Drury Lane Theatre management, particularly Richard Brinsley Sheridan and his son Thomas Sheridan, whom they represent as corrupt caretakers of that institution and of the national drama.